Fabrication and mechanical properties of self-reinforced poly(ethylene terephthalate) composites (eXPRESS Polymer Letters, 2011)
Self-reinforced poly(ethylene terephthalate) (PET) composites prepared by using a modified film-stacking technique were examined in this study. The starting materials included a high tenacity PET yarn (reinforcement) and a low melting temperature biodegradable polyester resin (matrix), both of which differ in their melting temperatures with a value of 56°C. This experiment produced composite sheets at three consolidation temperatures (Tc: 215, 225, and 235°C) at a constant holding time (th: 6.5 min), and three holding times (3, 6.5 and 10 min) at a constant consolidation temperature of 225°C. This study observed a significant improvement in the mechanical properties obtained in self-reinforced PET composites compared to the pure polyester resin. The results of tensile, flexural, and Izod impact tests proved that optimal conditions are low consolidation temperature and short holding time. The absorbed impact energy of the best self-reinforced PET composite material was 854.0 J/m, which is 63 times that of pure polyester resin.